Photostimulated passivation of spectrometric CdZnTe detectors - Zagoruiko, Yu.A.; Kovalenko, N.O.; Fedorenko, O.A.; Komar, V.K.; Sulima, S.V.; Dobrotvorskaya, M.V.; Terzin, I.S. (Functional Materials, 2008)
A method is proposed for side surface passivation of spectrometric detectors based on Cd ₁₋ₓZn ₓTe solid solution. The influence of photostimulated passivation treatment on electrical and spectrometric properties of the detectors has been established. Considered are the processes occurring on the crystal surface at the treatment and causing changes in the surface phase composition.